Risk perception about communicable and vector borne diseases among international travellers to Pakistan: a cross sectional study - Saeed, Sara; Tahir, Qandeel; Babar Kawish, Ayesha (Journal of the Pakistan Medical Association, 2024)
With the increase in air travel, the risk of diseases travelling from one geographical area to another has also increased. Relatively little is known about how travellers know and perceive the health risks associated with travel and how they adopt preventive measures before and while travelling abroad. The objective of this study is to determine the risk perception about communicable and vector-borne diseases among international travellers arriving from different countries and to find any association between the level of risk perception and independent variables. A cross-sectional study was conducted with 426 participants enrolled through convenient sampling technique. An already validated questionnaire was used to collect information. Chi square test was applied to ascertain any significant association between dependent and independent variables. Out of 426 respondents, only 226 (53%) had a high risk perception, whereas 220 (47%) had a low risk perception. —Continue